(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
IoT technology required to build smart homes, regarding automation and control processes, represents a significant information security and personal data protection challenge. Smart homes demand a new level of security requirements as they contain relevant, vulnerable and private information. Since IoT technology offers opportunities and imposes risks, an IoT based smart home is susceptible to the IoT security vulnerabilities and attacks via Internet. Personal data covering household habits could easily become available to the third parties without data subject consent. The business model created by the smart home technology industry based on sharing the house owners’ data with third parties is now facing significant obstacles with regard to data protection regulation and practice being developed in European Union. This paper indicates potential threats and points out current regulatory provisions regarding preserving data privacy and information security in the IoT smart home environment. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.